Guy de Maupassant - Lloyd, Christopher, 1953- (Reaktion Books, 2020)
"The most celebrated French storyteller of the nineteenth century, Guy de Maupassant was a master of the modern short story. The enduring appeal of his stories, which offer an intriguing picture of French life, derives from understated artistry, extreme craftmanship and the universality of his characters and their aspirations and misfortunes. In this insightful and compelling biography, the only one in English currently available, Christopher Lloyd situates Maupassant's work in the literary and social context of nineteenth-century France. Lloyd skillfully introduces the reader to Maupassant's most famous works, such as Boule de suif, Bel-Ami, and Pierre et Jean, and highlights the important stages and achievements of his life and legacy"--Back cover